Sweden : Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on the following topics; Monetary and Financial Policy Transparency, Banking Supervision, Securities Regulation, Insurance Regulation, and Payment Systems. (IMF Staff Country Reports; Country Report ;, 2002)
This paper presents key findings of Sweden's Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on Monetary and Financial Policy Transparency, Banking Supervision, Securities Regulation, Insurance Regulation, and Payment Systems. The assessment reveals that Sweden has an advanced and overall sound financial system that complies well with international standards and codes. Sweden confronts an environment that is less benign than in recent years and one that poses a number of challenges both to banks themselves and to the regulators and supervisors.